Effect of the implementation levels of the physical education program on health-related physical fitness of children in Selangor, Malaysia - Aboshkair, Kamil Abid Alhussain (2012)
The purpose of this study is to assess the implementation level of the physical education program in secondary schools in Selangor, and to determine the effect of the implementation level on the students’ health-related physical fitness. The checklist total score was used by 56 experienced physical education teachers from 38 selected schools to evaluate the implementation level. A pilot study test was conducted to identify any ambiguities, and ensure the suitability of the checklist questionnaire. Accordingly, the implementation level was categorized into three classes: high, moderate, and low. Based on this categorization, three different implementation levels of schools were selected randomly as samples of the study. The effect of the implementation level was determined by comparing the pre-and posthealth-related physical fitness performance (push-up, sit-and-reach, 7-stage sit-up, and 20m shuttle run) of the students. In all, 918 children (459 boys and 459 girls) participated in the present study. Three different age groups were assigned for 13-, 14-, and 16-year old students from each of these three different implementation levels schools. Each group consisted of 102 students (51 boys and 51 girls). Anthropometric measurements and other covariates [height, weight, body mass index (BMI), maturity status, family income, time spent within and outside school hours, and race] were measured or constructed to control the differences among the students in the statistical analysis. The results obtained from the first part of the study suggested that overall program content and policy had been implemented moderately, as planned by the Ministry of Education. The biggest problems faced by physical education teachers in running the physical education program were related to this area of the program: the inadequacy in the number of qualified physical education teaching staff, involvement of students in the physical education program, quality of the students, and apathy of the students. The results also indicated that the overall adequacy of the facilities offered by the schools to the physical education program was merely adequate. Significant effects of the implementation levels on the health-related physical fitness performance of boys and girls from all age groups were observed. However, the healthrelated physical fitness tests affected were not consistent across all age groups. Among the boys, the school with high implementation level reported an enhanced performance in push-ups by the 13-year-old students and sit-and-reach and sit-ups by the 14-year-old students, whereas, the performances of the 16-year-old students were enhanced in all physical fitness activities, except for the 20m shuttle run. Among the girls, the school with high implementation level enhanced the performance of sit-and-reach only in the 13-year-old students; sit-and-reach, sit-ups and 20 m shuttle runs in the 14-year-olds;and push-up in the 16-year-old students. The effect of high implementation level on the students varied. The boys in the 16-year-old group demonstrated a better performance in all health-related physical fitness activities than the two younger age groups, except in the 20m shuttle run, whereas the girls from the 14-year-old group showed better performance in sit-and-reach, sit-ups, and 20m shuttle run than did the girls in the 13-year-old group. To conclude, different implementation levels have affected students’ health-related physical fitness. Students’ health fitness increases if schools implemented high quality physical education program. Based on that, multiple plans needed to ensure high quality physical education program in schools.